ROLE OF JUDICIARY IN REFORM AND DEVELOPMENT OF INDIAN PRISON SYSTEM - Malik, Vinit Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The judiciary has a crucial role in the reform and advancement of the Indian jail system, serving as a catalyst for safeguarding inmates' rights and enhancing prison conditions. This article examines the proactive approach used by the judiciary in tackling systemic problems like as overpopulation, inadequate legal assistance, and inhumane circumstances in Indian jails. The courts have highlighted the basic rights of prisoners protected by the Indian Constitution, namely under Articles 14, 19, and 21, via significant rulings and instructions. Notable cases like Hussainara Khatoon v. Home Secretary, State of Bihar (1979), Ramamurthy v. State of Karnataka (1997), and In re: Inhuman Conditions in 1382 Prisons (2017, 2020) have emphasized the need of expeditious trials, the availability of complimentary legal assistance, and the compassionate treatment of incarcerated individuals. In addition, the judiciary's engagement has resulted in the development of policies with the goal of reducing overcrowding in prisons, enhancing medical services, and safeguarding the well-being of prisoners' families. This essay emphasizes the significant role of the court in promoting fair and compassionate jail systems in India by carefully examining and evaluating these judicial statements and their consequences. The judiciary's endeavors not only maintain the supremacy of legal principles but also foster a climate of human rights and reverence inside the correctional system, thereby advancing the wider objectives of social justice and transformation.